Controlled release dexamethasone implants in the round window niche for salvage treatment of idiopathic sudden sensorineural hearing loss - Plontke, Stefan K. (2014)
OBJECTIVE: To evaluate the feasibility and hearing outcome of a biocompatible degradable dexamethasone releasing implant for continuous drug delivery to the round window membrane in patients with idiopathic sudden sensorineural hearing loss (ISSHL) and insufficient recovery after systemic high dose glucocorticoid therapy. PATIENTS: Five patients with profound or moderate to severe hearing loss after systemic high dose prednisolone for ISSHL received local salvage therapy with a controlled release dexamethasone implant in the middle ear. INTERVENTION: Pieces of a sterile rod shaped poly(D,L-lactide-co-glycolide) PLGA polymer matrix containing a total of 0.7 mg dexamethasone which is approved for intravitreal use were implanted into the round window niche. MAIN OUTCOME MEASURE(S): Intraoperative handling and feasibility and hearing recovery as measured by change in pure tone threshold, final word recognition score and categories of improvement were evaluated. RESULTS: The implants were surgically placed without major difficulties. The mean hearing threshold significantly improved at follow up by 31±31 dB HL (from 94±27 to 63±36 dB HL; p<0.05). Two of five patients recovered completely. One patient showed partial hearing recovery with serviceable hearing. CONCLUSIONS: Although no drugs are currently approved for local therapy of inner ear disorders, there is increasing evidence that intratympanic glucocorticoids are effective as salvage therapy in ISSHL. The present study has shown encouraging results with a biodegradable polymer delivery system, demonstrating the translation of preclinical studies with controlled drug delivery into clinical practice.